Aerospace. Screws, 100° reduced countersunk head, internal offset cruciform ribbed or unribbed drive, normal shank, short or medium length MJ threads, metallic material, coated or uncoated, strength classes less than or equal to 1100 MPa. Dimensions. (15th March 1997) - British Standards Institution,
No abstract available